Study on separation and dynamic characteristics of ilmenite and chlorite regulated by structural parameters of spiral chute - Shuling Gao; Bochao Li; Chunyu Liu; Qian Wang; Xiaohong Zhou; Guixia Fan; Daoguang Teng (Minerals Engineering, 2026)

Inversion of Sound Speed Profile Controlled by Sparse Observations: Research Background, Current Status and Technical Analysis - Haopeng Fan; Shuling Xie; Shuqiang Xue (Oceans, 2026)
The sound speed profile (SSP) is a core environmental parameter for underwater acoustic detection, navigation, communication, and other applications. However, its accurate acquisition is constrained by the sparsity of observational data and the ill-posed nature of inversion problems. This paper systematically reviews the research progress of SSP inversion under sparse observation constraints. The review traces the technical evolution from early physical models to current intelligent paradigms, classifies and compares mainstream inversion methods, presents typical application scenarios with quantitative case studies, provides a comparison of all kinds of SSP acquisition routes, and discusses critical challenges and future trends. The review reveals that current AI-driven methods achieve a practical accuracy of approximately 1–2 m/s but face bottlenecks in interpretability, cross-regional generalization, and extreme-condition robustness. Fusing physical constraints with multi-source sparse data (remote sensing, in-situ discrete measurements) emerges as the core direction for balancing inversion accuracy, efficiency, and cost. This paper provides a comprehensive reference for technical selection in marine acoustics, ocean observation, and underwater operations.

Ni2P/Cu3P bimetallic phosphide embedded in nitrogen-doped carbon as SIB anode: Constructed hetero interface promoting fast Na+ diffusion and storage performance - Shuling Liu; Qiangqiang Shi; Xinyue Liu; Jiaru Fan; Lei Ren; Jianbo Tong (Chemical Engineering Journal, 2024)

Self-sacrificed construction of versatile nanoadjuvant for synergistically enhanced immunogenic cell death and improved anti-tumor immunity - Peng Hu; Xiaowen Peng; Shuang Zhao; Fan Li; Guoye Yang; Wujie Guo; Shuling Yu; Jianjun Cheng; Juan Cen; Jiahua Shi (Chemical Engineering Journal, 2024)

A Three-dimensional Anisotropic Creep Model for Predicting the Time-dependent Deformation of Layered Rock Mass - Shuling Huang; Jinxin Zhang; Xiuli Ding; Gang Han; Peiyang Yu; Xuanting Fan (Rock Mechanics and Rock Engineering, 2024)

Unraveling the molecular mechanisms of selenite reduction: transcriptomic analysis of Bacillus reveals the key role of sulfur assimilation - Ying Yang; Jiawei Jing; Shuling Fan; Zhuo Chen; Yuanyuan Qu (Biotechnology Letters, 2023)

Different toxicity to liver and gill of zebrafish by selenium nanoparticles derived from bio/chemical methods - Shuling Fan; Ying Yang; Lu Sun; Bin Yu; Chunxiao Dai; Yuanyuan Qu (Environmental Science and Pollution Research, 2022)

Correction to: Data-driven analysis and evaluation of regional agriculture for high quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Data-driven analysis and evaluation of regional agriculture for high-quality development of Anhui Province in the Yangtze River Delta - Fan Liu; Cui Wang; Yingyan Zhang; Shuling Zhou; Yaliu Yang; Xue Wu; Fagang Hu; Conghu Liu (Environmental Science and Pollution Research, 2022)

Differential Immune Responses and Protective Effects in Avirulent Mycobacterial Strains Vaccinated BALB/c Mice - Laicheng Liu; Ruiling Fu; Xuefeng Yuan; Chunwei Shi; Shuling Wang; Xianyu Lu; Zhao Ma; Xiaoming Zhang; Weiyan Qin; Xionglin Fan (Current Microbiology, 2015)